Comprehensive Carbon Footprint Assessment Using EPA and DEFRA: A Case Study of Bursa Technical University - Shahın, Somaia; Ozturk, Samet (My University, 2025)
Bursa Technical University (BTU) is committed to achieving sustainability goals and has taken significant steps in this direction. This study was conducted in accordance with the emission factors of the Environmental Protection Agency (EPA) and the conversion factors of the Department of Environment, Food and Rural Affairs (DEFRA). The study was carried out in line with International Organization for Standardization (ISO) 14064 and ISO 14001 standards and in harmony with the Sustainable Development Goals (SDGs), drawing on the experiences of five Turkish universities. This paper provides detailed information on BTU's carbon footprint calculation methodology, the standards used, and its alignment with the SDGs. The application of two distinct emission factors, those of EPA and DEFRA, yielded divergent carbon footprint (CF) values for BTU. The EPA approach yielded a value of 2697 tCO2e while the DEFRA-based assessment resulted in a lower CF of 1526 ton of CO2 equivalent (tCO2e). It is noted that most of the carbon emissions in the university is due to electricity consumption followed by natural gas usage. A prioritized action plan could be reducing the electricity consumption with automated lighting and laboratory equipment, subsequently increasing energy efficiency in the buildings.
Keywords: Sustainability; Carbon Footprint; EPA; DEFRA; SDGs; GHG